PENGGUNAAN MEDIA PROMOSI DIGITAL GUNA MENINGKATKAN PENJUALAN ALIYAH CAKE - Fatimah, Siska Ernawati; Purdianto, Ario; Firasati, Aoliyah (Transpublika Publisher, 2022)
The economic instability following the pandemic has had an impact on small businesses, including Micro, Small, and Medium Enterprises (MSMEs), which have experienced a decline in income and even bankruptcy. Therefore, strategies are needed for MSMEs to survive and develop their businesses. One of the MSMEs in Cirebon City affected by Covid-19 is Aliyah Cake, a snack business that offers various snacks with unique flavors and shapes. The business has faced challenges in its promotional efforts, resulting in a decrease in sales. The objective of this MSME program is to provide education and assistance in digital promotion, with the hope of increasing sales and the number of customers. The empowerment activities for MSMEs will be carried out for a period of 2 months, from November 2021 to December 2021. The results obtained after implementing the program show that Aliyah Cake is now able to independently conduct digital promotions by creating attractive photos or videos, which have generated visually appealing content that attracts buyers.